2015
DOI: 10.1021/nl504189p
|View full text |Cite
|
Sign up to set email alerts
|

Redox Sorting of Carbon Nanotubes

Abstract: This work expands the redox chemistry of single-wall carbon nanotubes (SWCNTs) by investigating its role in a number of SWCNT sorting processes. Using a polyethylene glycol (PEG)/dextran (DX) aqueous two-phase system, we show that electron-transfer between redox molecules and SWCNTs triggers reorganization of the surfactant coating layer, leading to strong modulation of nanotube partition in the two phases. While the DX phase is thermodynamically more favored by an oxidized SWCNT mixture, the mildly reducing P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
125
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(129 citation statements)
references
References 22 publications
3
125
0
1
Order By: Relevance
“…The oxidation of the SWCNTs observed in SDS and SUS solution should alter the density of the coating layer of the surfactants on the SWCNTs because the adsorbability of SWCNTs dispersed by SDS onto the hydrogel is reduced by decreasing the pH value, that is, oxidation with the O 2 /H 2 O couple . Recently, it was also reported that the adsorbability onto hydrogels was reduced by the addition of NaClO . On the basis of these results, we suggest that more oxidized SWCNTs have more surfactant molecules on the SWCNT surfaces.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…The oxidation of the SWCNTs observed in SDS and SUS solution should alter the density of the coating layer of the surfactants on the SWCNTs because the adsorbability of SWCNTs dispersed by SDS onto the hydrogel is reduced by decreasing the pH value, that is, oxidation with the O 2 /H 2 O couple . Recently, it was also reported that the adsorbability onto hydrogels was reduced by the addition of NaClO . On the basis of these results, we suggest that more oxidized SWCNTs have more surfactant molecules on the SWCNT surfaces.…”
Section: Discussionmentioning
confidence: 58%
“…[23] Recently, it was also reported that the adsorbability onto hydrogels was reduced by the addition of NaClO. [22] On the basis of these results, we suggest that more oxidized SWCNTsh ave more surfactantmolecules on the SWCNT surfaces. In fact, the MD simulationsr evealed an increased number of the surfactants in the vicinity of the oxidized SWCNT (Table 2).…”
Section: Redox-dependent Assembly Formation Of Surfactants On the Swcmentioning
confidence: 68%
See 3 more Smart Citations